2001
DOI: 10.1001/jama.285.5.652
|View full text |Cite
|
Sign up to set email alerts
|

Research Advances in Pemphigus

Abstract: Pemphigus is an autoimmune disorder, known to be caused by autoantibodies directed against critical adhesion molecules of squamous epithelial cells, the desmogleins. These autoantibodies induce blistering of skin and mucosal surfaces and lead to severe morbidity and, potentially, death. Key factors include associated major histocompatibility complex class II genes, the structure of the desmoglein antigens, and the role of autoantibody in impairing cellular adhesion. This article discusses the precise structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Anti-epidermal autoantibodies, present in PV patient sera and easily detected by immunofluorescence (IF) on perilesional epidermis, are pathogenic; PV IgG reproduces the clinical, histologic, and immunologic features of the disease when passively transferred to neonatal mice. Pathogenic PV autoantibodies bind the dsg3 ectodomain in a calcium-dependent immunological reaction (6).…”
mentioning
confidence: 99%
“…Anti-epidermal autoantibodies, present in PV patient sera and easily detected by immunofluorescence (IF) on perilesional epidermis, are pathogenic; PV IgG reproduces the clinical, histologic, and immunologic features of the disease when passively transferred to neonatal mice. Pathogenic PV autoantibodies bind the dsg3 ectodomain in a calcium-dependent immunological reaction (6).…”
mentioning
confidence: 99%
“…These results again point to the idea that El Bagre EPF represents a novel variant of the disease. Nevertheless, the mechanism by which recognition of Dsg-1, and perhaps other antigens, contributes to the observed apoptosis [8, 9] and development of lesions in EPF is not known [1]. …”
Section: Immunologic Features Of El Bagre Epfmentioning
confidence: 99%
“…Most autoimmune diseases, including PV and PF, occur sporadically and are widely scattered geographically. However, endemic pemphigus foliaceus (EPF) represents an autoimmune disorder that is limited to a well-defined geographic area (reviewed in [1, 2]), such as Brazil or, as reviewed below, El Bagre, Columbia in South America [3]. This El Bagre EPF is also characterized by acantholytic skin lesions and by autoantibodies to Dsg-1 [3–5].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, PF affects only the skin, whereas PV initially affects mucous membranes (mucosal PV) and later involves the skin (mucocutaneous PV) [1, 3, 4]. The hallmark of all pemphigus phenotypes is the presence of intraepidermal vesicles [1] and anti-epidermal autoantibodies [2, 3, 5-7]. The anti-epidermal autoantibodies are detected bound to the surface of detached keratinocytes in lesional epidermis and circulating in the serum of patients [7].…”
Section: Introductionmentioning
confidence: 99%
“…The anti-epidermal autoantibodies are detected bound to the surface of detached keratinocytes in lesional epidermis and circulating in the serum of patients [7]. It has been well demonstrated that these anti-epidermal autoantibodies recognize desmogleins (Dsg), a family of desmosomal cell adhesion glycoproteins [1, 2, 5-7]. The desmosome is a cell-cell adhesion organelle present in keratinocytes and other squamous epithelial cells [8], and consists of core and plaque structural components.…”
Section: Introductionmentioning
confidence: 99%